Spatial and temporal distribution and ecological risk assessment of typical antibiotics in natural and wastewater of Jinjiang River Basin. - Meng Wang; Jiale Li; Yongkang Zhou; Wenjia Zhou; Shuai Huang (PLoS ONE)
Antibiotics are widely used in human medical, livestock, and aquaculture fields. Most antibiotics are water-soluble and cannot be fully absorbed by humans or animals. If feces or wastewater containing antibiotics are improperly treated or discharged directly into surface water or groundwater, it will undoubtedly have an impact on aquatic organisms. The Ganjiang River is the largest river in Jiangxi Province and the largest tributary of Poyang Lake Basin. Jinjiang River, a tributary of Ganjiang River, is a typical livestock and poultry breeding area in the Poyang Lake Basin, along which many townships and counties are distributed. Gao'an and Shanggao counties are important agricultural and animal husbandry production areas in Jiangxi Province. In this paper, automatic solid phase extraction-ultra high performance liquid chromatography-mass spectrometry (SPE-UPLC-MS/MS) technology was used to simultaneously detect 27 antibiotics in 5 categories of macrolides, tetracyclines, quinolones, nitroimidazoles and sulfonamides in water. Based on this method, the concentrations and distributions of these antibiotics were analyzed. Ecological risk assessment of the Jinjiang River Basin was conducted using the ecological risk quotient method, aiming to supplement antibiotic data in the Jinjiang River Basin and provide scientific basis for local ecological environment management. The research results indicate that from 2019 to 2021, two years later, there was an increase in the use of Sulfadiazine and Roxithromycin in the Jinjiang River Basin, while the usage of Ciprofloxacin and Oxytetracycline was relatively low. In 2021, out of the 27 antibiotics, 24 were detected in surface water, 20 in groundwater, and all in wastewater. Among them, Sulfamethoxazole was the most widely used antibiotic, primarily in livestock and poultry farming. Gao'an City, a key breeding area in the Jinjiang River Basin, exhibited the highest concentration of Sulfamethoxazole at 409.96 ng·L-1, which far exceeds other antibiotics and warrants significant attention. A comparison of surface water concentrations between the Jinjiang River and 12 other regions revealed higher overall pollution levels of Roxithromycin and Sulfamethoxazole. Furthermore, according to the ecological risk assessment results, only Sulfamethoxazole poses a moderate risk to aquatic organisms.